EFFECT OF POPULATION ADMINISTRATION SERVICE WORKLOAD AGAINST EMPLOYEE PERFORMANCE (STUDY AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF JEMBER REGENCY) - Hepiastuti, Selvi Budi; Suryawati, Dina; Fauziah, Luly (Universitas Pelita Harapan, 2022)
The purpose of this research is to examine the effect of workload population administration services on the performance of employees in the Population and Civil Registration Service of Jember Regency. Based on preliminary observation data on the performance of employees of the Population and Civil Registration Service of Jember Regency, they managed to get the 2nd place achievement nationally, but employees felt a workload when doing work. This study used an explanatory quantitative approach. The subjects used in this study were employees of the Population and Civil Registration Service of Jember Regency, totaling 29 employees. Analysis data used simple linear regression statistics. The results showed that workload has a positive effect on employee performance. That stuff explains that increasing workload will affect the improvement of employee performance. The agency should pay attention to the workload given to each employee according to their abilities so that employees will feel more comfortable doing work.